PRELIMINARY STUDY OF COAL RESOURCES POTENTIAL IN BESIQ AREA AND SURROUNDINGS, KECAMATAN DAMAI, KUTAI BARAT REGENCY, EAST KALIMANTAN - Hadis Sakti Hasyimi (Jurnal Scientia, 2023)
The study area in Kecamatan Damai, Kabupaten Kutai Barat, East Kalimantan, consists of two coal-bearing formations, namely the Pamaluan Formation (Tomp) and the Warukin Formation (Tmw). The northern region is characterized by moderate to steep hills with slopes ranging from 7% to 30%. The lithology predominantly comprises sandstone with some claystone, and coal is found as intercalations within these layers. Five coal outcrops, named OCPDM, were identified, with three located outside the concession area. These outcrops exhibit varying thicknesses and orientations, primarily following a northeast-southwest direction, representing four coal seams of moderate thickness. The coal samples show low-quality characteristics. An analysis revealed that only Seam 2 and Seam 3 extend throughout the concession area, with an inferred coal resource of up to 18,100 metric tons. However, the preliminary investigation yielded unsatisfactory results, indicating that the coal potential in the area is not economically viable. Furthermore, constructing a hauling road to the nearest designated stockpile location at Mahakam River would pose significant challenges in terms of distance and cost. Considering these factors, it is concluded that the area does not hold sufficient economic potential for coal extraction.